Living Hadith of Jaburan Tradition in the Month of Ramadan for the People of Randegan Village, Banyumas Regency - Yurianto, Ramdhan; Faizatun Nafi’ah, Zahra; Hayatul Alfath, Fitriani (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
Jaburan is the tradition of giving food to break the fast or for people who perform qiyam lail, either reading the Qur'an or I'tikaf in mosques after tarawih prayers in Banyumas Regency. The implementation of the Jaburan tradition is carried out structurally divided per resident in each prayer room and designed per week according to the number of people living in the mosque or mosque environment. This study uses living hadith theory and phenomenological theory to observe the procession of Jaburan tradition which is carried out at the time of breaking the fast and after tarawih prayers. The existence of jaburan is also the result of understanding the substance of the hadith of the Prophet PBUH. The practice of Jaburan is carried out with love and affection for others by sharing the best food. Likewise, the meaning behind the implementation of the Jaburan tradition is: 1) increasing devotion to Allah; 2) implementing the sunnah in accordance with what is stated in the hadith; 3) fostering a sense of sharing and social care; 4) Efforts to compete in the hunt for rewards in the Ramadan month and 5) preserving old traditions carried out by the people of the Banyumas area.